Development and implementation of a municipal outdoor play policy for children and youth in Nova Scotia, Canada: a community case study - Caldwell, Hilary A. T.; Arthur, Mike; Simms, Ashley; Mawhinney, Hannah; Hancock Friesen, Camille L.; Kirk, Sara F. L. (Frontiers in Public Health, 2024)
Background: Children and youth benefit from outdoor play; however, environments and policies to support outdoor play are often limited. The purpose of this paper is to describe a case study of the development of a municipal outdoor play policy in Nova Scotia, Canada. Methods: The outdoor play policy was developed by the Town of Truro with support from the UpLift Partnership, a School-Community-University Partnership in Nova Scotia, Canada. UpLift supports the health and wellbeing of school-aged children and youth using a Health Promoting Schools approach which identifies the important role of municipal government in creating healthy school communities. The UpLift Partnership and the municipality hosted online workshops for municipal staff, community leaders and partners that included content about the importance of outdoor play, barriers and facilitators to outdoor play, best practices for youth engagement, the policy development process, and how policy actions can support outdoor play. Workshop participants developed policy actions for their community of Truro, Nova Scotia to increase opportunities for outdoor play for children and youth. Results: Following the workshops, a small team from the municipality and UpLift drafted an outdoor play policy and submitted it to Truro town council for approval. The outdoor play policy was adopted in Fall 2021 and has since informed recreation and municipal planning decisions. Conclusions: By presenting a case study of the development of this outdoor play policy, we hope other communities may be inspired to develop and adopt their own outdoor play policies to benefit children and youth in their communities.